2019
DOI: 10.30931/jetas.504837
|View full text |Cite
|
Sign up to set email alerts
|

Substrate to Nozzle Distance Influence on the Properties of Zinc Oxide Films Formed with Chemical Spray Pyrolysis Technique

Abstract: In this work, the zinc oxide (ZnO) thin films have been deposited on the substrate glass via chemical spray pyrolysis technique that influence of the distance between nozzle and substrate on the optical, morphology, chemical composition and structural properties of two samples. Thicknesses of two samples were obtained around 300 (nm) via weighing method at a stable substrate temperature of 370 °C. Crystal structure was investigated by manner of an X-Ray Diffraction (XRD); it was found that two films have three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The present study used a chemical spray approach to deposit nickel-doped zinc oxide thin films In another study by (13), they found quality crystal rather than we reported the electrochemical supercapacitor performance Hematite α-Fe2O3 thin films prepared by spray pyrolysis from a non-aqueous medium.…”
Section: Film Preparationmentioning
confidence: 64%
“…The present study used a chemical spray approach to deposit nickel-doped zinc oxide thin films In another study by (13), they found quality crystal rather than we reported the electrochemical supercapacitor performance Hematite α-Fe2O3 thin films prepared by spray pyrolysis from a non-aqueous medium.…”
Section: Film Preparationmentioning
confidence: 64%
“…Generally, its decrease results in a denser and smoother film due to the increased heat and mass transfer efficiency [327]. Omar [328] studied the influence of the distance between the nozzle and substrate on the morphological, structural, chemical composition, and optical properties of ZnO thin films deposited using the SP technique. The morphology of the thin film was examined using Scanning Tunnelling Microscopy (STM), and it was observed that reducing the nozzle-substrate distance led to an increased root mean square (rms) roughness.…”
mentioning
confidence: 99%